2002
DOI: 10.1017/s0022336000041986
|View full text |Cite
|
Sign up to set email alerts
|

Crinoid distribution and feeding morphology through a depositional sequence: Kope and Fairview formations, Upper Ordovician, Cincinnati Arch region

Abstract: Crinoid columnals are major faunal components of interbedded shales and carbonates of the Upper Ordovician Kope to Fairview formations (Edenian-Maysvillian) of the Cincinnati Arch region. Six species can be identified on the basis of distinctive morphological characters of the columnals. Crinoid distribution was plotted from point-counted carbonate samples taken through a 68-m thick composite section of the Kope to Fairview formations in Campbell County, Kentucky. This section spans a shallowing-upward, third-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…Morphologically, crinoid features are well represented in the skeleton, so relatively little information is lost with the decay of soft tissues (Ausich 2001). Although the crinoid skeleton requires special circumstances to be preserved intact (Donovan 1991;Brett et al 1997;Ausich 2001), many species, especially during the early Paleozoic, can be identified from disarticulated elements alone (Brower and Veinus 1974;Meyer et al 2002), and thus, taxa from environments that have lower preservation potential can be included in morphologic investigations. Even within a cohesive guild of sessile passive suspension feeders, crinoids exhibit many different features for obtaining resources (Kammer and Ausich 1987).…”
Section: Methodsmentioning
confidence: 99%
“…Morphologically, crinoid features are well represented in the skeleton, so relatively little information is lost with the decay of soft tissues (Ausich 2001). Although the crinoid skeleton requires special circumstances to be preserved intact (Donovan 1991;Brett et al 1997;Ausich 2001), many species, especially during the early Paleozoic, can be identified from disarticulated elements alone (Brower and Veinus 1974;Meyer et al 2002), and thus, taxa from environments that have lower preservation potential can be included in morphologic investigations. Even within a cohesive guild of sessile passive suspension feeders, crinoids exhibit many different features for obtaining resources (Kammer and Ausich 1987).…”
Section: Methodsmentioning
confidence: 99%
“…Its depositional environment has been interpreted as between storm wave base and normal wave base in the transitional or deep subtidal zone (Meyer et al, 2002). The Fairview Formation intertongues with and is overlain by the Miamitown Shale, which is dominated by medium to thick shales interbedded with thin limestones (Dattilo, 1998).…”
Section: Geologic Settingmentioning
confidence: 99%
“…Previous citations of camerates from the Kope Formation are poorly constrained. Glyptocrinus columnals were reported from the uppermost Kope Formation (indicative of shallowing) (Meyer et al, 2002), and Pycnocrinus pattersoni (Miller, 1882) was reported by Dalvé (1948) in the lower Kope (Economy Member) (later workers, Bassler andMoodey, 1943 andWebster andWebster, 2014 re-assigned this occurrence of P. pattersoni to the sub-Kope Point Pleasant tongue of the Clays Ferry Formation [formerly Cynthiana Formation]). Although Glyptocrinus had not been reported previously from deep-water facies in the Kope Formation, Brett et al (2008b, p. 46) and Brower (2011) reported glyptocrinids from a relatively deep-water setting in the Rust Formation of New York (Katian).…”
Section: Assemblage Paleoecologymentioning
confidence: 99%